Why women do not utilize maternity services in Nepal: a literature review. - Karkee, R.; Lee, A.; Binns, Colin (2013)
The structure and provision mechanism of maternity services in Nepal appears to be good, with adequate coverage and availability. Utilization of maternity services has also improved in the past decade. However, this progress may not be adequate to achieve the Millennium Development Goal to improve maternal health (MDG 5) in Nepal. This paper reviews the factors that impede women from utilizing maternity services and those that encourage such use. Twenty-one articles were examined in-depth with results presented under four headings: (i) sociocultural factors; (ii) perceived need/benefit of skilled attendance; (iii) physical accessibility; and (iv) economic accessibility. The majority of the studies on determinants of service use were cross-sectional focusing on sociocultural, economic and physical accessibility factors. In general, the education of couples, their economic status and antenatal check-ups appeared to have positive influences. On the other hand, traditional beliefs and customs, low status of women, long distance to facilities, low level of health awareness and women's occupation tended to impact negatively on service uptake. More analytical studies are needed to assess the effectiveness of the Safer Mother Programme, expansion of rural birth centres and birth-preparedness packages on delivery-service use. Moreover, it is important to investigate women's awareness of the need of facility delivery and their perception of the quality of health facilities in relation to actual usage.